EFISIENSI ANGGARAN DI ERA PEMERINTAHAN BARU: PERSEPSI MAHASISWA TERHADAP DAMPAKNYA BAGI PENDIDIKAN DAN KESEJAHTERAAN - aulia, annisa; Ardina Febriyanti, Ardina; Syahrani Anggitasari, Syahrani; Ramzi Zahid Muzahffar, Ramzi; Joko Tri Nugraha, Joko (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2025)
This study discusses students’ perceptions of the budget efficiency policy implemented in the era of the new government, focusing on its impact on the education and welfare sectors. Budget efficiency has become a strategic issue in state financial governance; however, its implementation often generates both pros and cons, especially in public services such as education. This research employs a quantitative descriptive method with a survey approach targeting active K3 students of the 2024 cohort in Public Administration, Faculty of Social and Political Sciences. The instrument used is a Likert scale-based questionnaire that encompasses aspects of understanding, attitudes, and perceptions of students towards the policy. The results show that the majority of respondents have a skeptical, even negative perspective toward the budget efficiency policy. As many as 75.8% respondents expressed disagreement or strong disagreement with the policy, mainly because it is considered to reduce the quality of educational services, does not guarantee equitable access to education, and does not involve community aspirations in its formulation process. Furthermore, the majority of students feel that the benefits of this policy have not been felt significantly by them as recipients of educational services. These findings indicate that the implementation of budget efficiency policies needs to be evaluated, both in terms of planning and execution, to achieve efficiency goals without sacrificing the quality and equity of public services. This study recommends an increase in transparency, public participation, and government communication to make the adopted policies more responsive to community needs.